Resource allocation towards Engineering Procurement Construction (EPC) fabrication oil and gas megaprojects: Exploring issues on cost overrun / Farrah Rina Mohd Roshdi ... [et al.] - Mohd Roshdi, Farrah Rina; Ismail, Kharizam; Lop, Nor Suzila; Ab Wahab, Lilawati (2022)
Nowadays, cost overrun is prevalent in building construction, infrastructure and oil and gas construction projects. In general, successful project management is a project that can manage resources well according to the project's needs. However, cost overrun can occur due to a lack of management in allocating resources to the correct activities in projects when they are operated. The resources commence with money or capital involving machinery, manpower, and materials to the right method arranged at the Procurement Phase. However, due to the adverse economic conditions and circumstances of the Malaysian oil and gas sector, it is vital to minimize costs, control costs and realign organizational mission towards resource allocation management. Thus, an optimal resource allocation must be made on a cost-effective basis to avoid cost overruns. Therefore, this research aims to explore several previous works of literature on oil and gas fabrication projects management, focusing on issues of cost overrun across the globe. The data was gathered from earlier studies on cost overrun in Oil and Gas megaprojects. The exploration revealed the primary relative importance of the theoretical framework; in the context of the Oil and Gas Industry by a country that focuses on cost overruns issues. This research is expected to raise concerns about the importance of resource allocation management, which is experiencing cost overrun of Oil and Gas Fabrication projects.